Ação social da Rede Caritas de Empreendimentos de Economia Solidária - EES: um estudo sobre valores e dinheiro - Mafra, Luciana Dantas (2013)
This study seeks to analyze the relationship between values and economic practices in social actions developed by the Caritas Network northeastern in projects linked to the Solidarity Economy over the last decade. This link between economic values and practices is discussed in relation to both Weber (Economy and Society) and Simmel (The Philosophy of Money) with a treatment of the affinities between both the economic sphere and religious ethics and the forms of sociability that bring individuals into contact with the circulation of money. The research scope was comprised of businesses monitored by Caritas in four northeastern states (Pernambuco, Paraíba, Alagoas and Rio Grande do Norte where we sought investigate the influence of ethical values, religious networks, and the economic practices of associations, groups and cooperatives. The field research took place over nine months with visits to local groups in their production areas, participation in trade fairs, training, exchanges, forums and regional meetings. Through this research we saw that money, the symbol and instrument of utilitarian reason, shapes individual behavior and socialization conditions since in business practices it is permeated by religious and ethical values when confronted by their experiences, values and neoliberal practices. The data and conclusions and relates to the overall research of the regional Caritas Network, the place it occupies in the Solidarity Economy and its influence on the sociability of business